Pengaruh Keputusan Investasi, Keputusan Pendanaan, Dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada PT Mayora Indah Tbk Periode 2015-2024 - Karliyah; Janudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of Investment Decision, Funding Decision, and Dividend Policy variables on Company Value at PT Mayora Indah Tbk. This research method is quantitative. The sample used is the financial report of PT Mayora Indah Tbk for 10 (ten) years. Based on the results of the T-test of Investment Decision on Company Value, it produces Tcount <Ttable (1.227 <2.306), this indicates that there is no significant effect between Investment Decision on Company Value. The results of Funding Decision on Company Value Tcount> Ttable (3.410> 2.306), so there is a significant effect between Funding Decision on Company Value. Meanwhile, Dividend Policy Results do not have a significant effect on Company Value Tcount <Ttable (0.942 <2.306). Furthermore, the results of the F-test indicate that investment decisions, funding decisions, and dividend policies together have a significant effect on Company Value, as indicated by Fcount> Ftable (10.326> 4.530).